On Weighted Banach Frames - Vashisht, L. K.; Sharma, Shalu (Communications in Mathematics and Applications, 2012)
We introduce and study weighted Banach frames in Banach spaces. Necessary and/or sufficient conditions for a weighted Banach frame to be exact are given. An application of weighted Banach frames is discussed.